The Conservation Relevance of Epidemiological Research into Carnivore Viral Diseases in the Serengeti - SARAH CLEAVELAND; TITUS MLENGEYA; MAGAI KAARE; DAN HAYDON; TIZIANA LEMBO; M. KAREN LAURENSON; CRAIG PACKER (Conservation Biology, 2007)
Recent outbreaks of rabies and canine distemper in wildlife populations of the Serengeti show that infectious disease constitutes a significant cause of mortality that can result in regional extirpation of endangered species even within large, well‐protected areas. Nevertheless, effective management of an infectious disease depends critically on understanding the epidemiological dynamics of the causative pathogen. Pathogens with short infection cycles cannot persist in small populations in the absence of a more permanent reservoir of infection. Development of appropriate interventions requires detailed data on transmission pathways between reservoirs and wildlife populations of conservation concern. Relevant data can be derived from long‐term population monitoring, epidemic and case‐surveillance patterns, genetic analyses of rapidly evolving pathogens, serological surveys, and intervention studies. We examined studies of carnivore diseases in the Serengeti. Epidemiological research contributes to wildlife conservation policy in terms of management of endangered populations and the integration of wildlife conservation with public health interventions. Long‐term, integrative, cross‐species research is essential for formulation of effective policy for disease control and optimization of ecosystem health.